Safety and efficacy of endovascular recanalization for symptomatic non-acute atherosclerotic intracranial large artery occlusion - Chu, Xi; Meng, Yao; Zhang, Jun; Sun, Lili; Yin, Hao; Dong, Kaiyue; Chen, Yingkun; Song, Yun; Zheng, Meimei; Wang, Wei; Zhao, Wei; Han, Ju (Frontiers in Neurology, 2023)
Background and objective The optimal treatment for patients with symptomatic non-acute atherosclerotic intracranial large artery occlusion (ILAO) despite medical treatment is not well established. We aimed to assess the safety, efficacy, and feasibility of angioplasty and stenting for these patients. Methods A total of 251 consecutive patients with symptomatic non-acute atherosclerotic ILAO treated with interventional recanalization were retrospectively collected in our center from March 2015 to August 2021. The rate of successful recanalization, perioperative complications, and follow-up outcomes were evaluated. Results Successful recanalization was achieved in 88.4% (222/251) of the patients. A total of 24 (24/251, 9.6%) symptomatic complications occurred among 251 procedures. In the 193 patients with clinical follow-up during 19.0 ± 14.7 months, 11 (11/193, 5.7%) patients developed ischemic stroke and four (4/193, 2.1%) patients developed transient ischemic attack (TIA). In the 106 patients with vascular imaging follow-up during 6.8 ± 6.6 months, seven (7/106, 6.6%) patients had restenosis and 10 (10/106, 9.4%) patients had reocclusion. Conclusion This study suggests that interventional recanalization may be a feasible, basically safe, and an effective alternative in carefully selected patients with symptomatic non-acute atherosclerotic ILAO who have failed medical management.